Back Cover: Cobalt‐Catalyzed C(sp2)−H Methylation by using Dicumyl Peroxide as both the Methylating Reagent and Hydrogen Acceptor (Chem. Eur. J. 35/2016). Issue 35 (4th July 2016) - Li, Qun; Li, Yanrong; Hu, Weipeng; Hu, Renjian; Li, Guigen; Lu, Hongjian
Abstract : A cobalt‐catalyzed direct methylation of the C(sp 2 )−H bond by using dicumyl peroxide as both the methylating reagent and hydrogen acceptor has been established. The molecule in the picture represents one of the key intermediates. The grey sphere represents the Co catalyst, which forms a Co−N bond and coordinates to the N atom of pyridine; the brown sphere represents a newly formed methyl group. The brown sphere in the phoenix's mouth (left) represents the methyl group which is used to replace a hydrogen atom in the molecule. The sphere in the mouth of the second phoenix represents the hydrogen atom which is replaced by a methyl group. More information can be found in the Communication by G. Li, H. Lu et al. onpage 12286 ff.